FACTORS AFFECTING EXECUTIVE THINKING OF PRESCHOOL-AGED CHILDREN IN CHILD DEVELOPMENT CENTER, RATCHABURI PROVINCE - Seamkhumhom, Duangruetai; Kamtubtim, Varaporn; Srisuantang, Sunti (Journal of MCU Nakhondhat, 2025)
This research aimed to study the executive Functions of preschool children by studying child factors, family factors and factors affecting executive Functions of preschool children in child development centers in Ratchaburi Province. The sample consisted of 300 pairs of preschool children and their parents who received services at the child development centers under the Department of Local Administration in Ratchaburi Province. Multi-stage random sampling was used. Data were analyzed using descriptive statistics and multiple regression analysis. The results of the research found that Executive Functions of preschool children was at a moderate level (M = 49.97, S.D. = 9.90). Factors that significantly affected executive thinking of children were parenting that promoted discipline (β = .170, p < .05), parenting that promoted inconsistent discipline (β = .136, p < .05), and parental stress (β = .133, p < .05). All variables together predicted executive thinking by 9 percent (R2 = .090, p < .05). The results of the research suggest that health personnel should provide knowledge to parents or caregivers about channels for assessing stress and finding solutions to stress in order to prevent the transmission of stress through childcare to children while at home. In addition, knowledge about childcare that promotes executive Functions should be provided so that parents have knowledge and understanding and can integrate it through organizing learning experiences while children are at home. For example, in raising children to promote discipline, parents should explain the reasons to children to acknowledge their mistakes calmly and understandably, and should give children the opportunity to find solutions by themselves to reduce the chances of repeating the same mistakes in the future.